PENGARUH PENDUDUKAN JEPANG TERHADAP MASYARAKAT MAGELANG 1942-1945 (History Department, Semarang State University and Historian Society of Indonesia, 2010)
Japan entered through Yogyakarta to Magelang, on March 6, 1942, unlike the Dutch who thought Japan estimation will come from Semarang. The arrival of Japan was warmly welcomed because people already feel hate with the Dutch who like to act arbitrarily. Japan imposed political policies of the economic system of war (kriegwierschaft) that everything is intended to meet the needs of war. Policies include deposit obligation of rice, romusha, taxes, changes in the system of government (decentralization). This policy affects the economy of the people who declined Magelang and adversely affects the condition of society and cause various problems of hunger, lack of clothing, poverty, and social problem from health problems and high death rates are very high. But there is also a positive impact such as the introduction of new rice planting system and the established system of Japanese school in Magelang. The young men in addition to getting a formal education also received military training which is beneficial for the survival struggle of the people of Magelang in the future. Key words: Japanese occupation, struggle, Magelang Jepang masuk melalui Yogyakarta ke Magelang, tepatnya tanggal 6 Maret 1942, tidak seperti perkiraan Belanda yang mengira Jepang akan datang dari arah Semarang. Kedatangan Jepang disambut baik karena orang sudah merasa benci Magelang dengan Belanda yang suka bertindak sewenang-wenang. Jepang menerapkan kebijakan politik dari sistem ekonomi perang (kriegwierschaft) yang semuanya dimaksudkan untuk memenuhi kebutuhan perang. Kebijakan yang mencakup pula kewajiban simpanan wajib beras, romusha, pajak, perubahan sistem pemerintahan (desentralisasi). Kebijakan ini mempengaruhi perekonomian masyarakat yang menolak Magelang dan berakibat buruk pada kondisi masyarakat dan menyebabkan berbagai masalah kelaparan, kekurangan pakaian, kemiskinan, dan masalah sosial dari masalah kesehatan dan tingkat kematian sangat tinggi. Tapi ada juga dampak positif adalah seperti mulai diperkenalkan dengan sistem tanam padi baru dan pendirian sekolah Jepang di Magelang. Orang-orang muda selain mendapatkan pendidikan formal juga menerima pelatihan militer yang bermanfaat bagi perjuangan hidup rakyat Magelang di masa depan. Kata kunci: pendudukan Jepang, perlawanan, Magelang